Justice league unlimited (DC Comics kids collection., 2005)
Under the leadership of the original Justice League, Earth's superheroes band together to form an unbeatable force that's always ready for action! These three exciting adventures from the hit TV show feature battles with a menacing nuclear robot, the egomaniacal child magician Mordred and the dangerous god of war Ares. In Justice League Unlimited, there's always a hero around when you need one!